LQ-45 STOCK PRICE REACTION EVENT STUDY ON EARNINGS ANNOUNCEMENT - Jaya Kusuma, Putu Sri Artha; Dewa Ayu, Sinta Dharmayanti (KRISNA: Kumpulan Riset Akuntansi, 2025)
The population in this study consisted of 153 manufacturing businesses listed on the Indonesia Stock Exchange in 2021–2023, with the goal of determining the stock price response to the earnings release of the LQ-45 stock index. In order to acquire 405 research data, a sample of 135 manufacturing organizations was utilized. Descriptive statistical analysis, the classical assumption test, and another test (Wilcoxon Signed-Rank) are the methods of analysis that are employed. According to the study’s findings, stock returns for manufacturing companies listed on the Indonesia Stock Exchange in 2021–2023 did not vary following their earnings announcements. Trade Volume Activity is positive and significant to earnings announcements of manufacturing companies listed on the Indonesia Stock Exchange in 2021 – 2023.